Conceptual Status of Non-Reference Use of Pronouns in the Literary and Critical Discourse of the 19th Century Writer N. D. Akhsharumov - S. Yu. Lavrova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The author uses personal and possessive pronouns in the literary and critical discourse of the 19th century writer and fiction writer N. D. Akhsharumov (1820-1893). The question is raised about the specificity of communicativeness of the pronouns used by the author, characterized by a wealth of referential and non-referential interpretations. The novelty of the study is seen in the fact that for the first time a discursive analysis of the reference of two categories of pronouns in literary and critical work, unknown to a wide circle of readers, is offered. The material of the study uses the literary and critical article “On the enslavement of art” (1858), which expresses the main aesthetic and ethical approaches of the writer to understanding creativity. A phased discursive analysis of personal and possessive pronouns is carried out with the identification of their basic functions: reference (deictic - anaphoric) and non-reference (conceptual). It is shown that when changing the function of pronouns from the reference to the non-reference, the text status of the language units also changes. It is proved that pronouns in the author’s context with non-reference use acquire the status of modus concepts of the author’s narration.